THE CREATION OF THE HERO IN DE BEAUVOIR’S SHE CAME TO STAY - SATRIO WAHYU PRATOMO (LITERA KULTURA : Journal of Literary and Cultural Studies, 2013)
In a novel, it is often found that there is a character which becomes a center of the attention. That character can be a good character or the bad one. In literature, this character is named The Hero. This study is used to reveal how the role of a hero in case of building a completed story is. The hero which will be analyzed here is the hero in She Came to Stay written by Simone de Beauvoir. To analyze the hero in that novel, two theories which are brought by Northrop Frye is used, Theory of Modes and Theory of Mythos. Both of those theories is really related to the creation of a story and the hero in it. By using Theory of Modes, it will be easy to understand the position of the hero which is created by the processes in the story such as becoming inferior and superior. Almost the same to last theory, Theory of Mythos also analyzes how the story creates the hero from another point or view. It sees the story in case of giving some conditions which will be experienced by the hero. Those conditions can create the hero. When Francoise becomes a hero, this study also sees that there will be some changes as some effects of becoming a hero. That becomes the focus also for this study. Keywords: hero, superiority, inferiority, innocent, experience